A lithium iron manganese phosphate composite positive electrode material and its preparation method and application

By using template agents in lithium-ion batteries to prevent particles from agglomerating and coat polymer electrolytes on the surface of lithium manganese iron phosphate composite positive electrode material, the problem of side reactions in the battery is solved and the electrochemical performance is significantly improved.

CN119786553APending Publication Date: 2025-04-08GTC-POWER ZHUHAI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411821207.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have side reactions with sulfide solid electrolytes, which damages battery performance. It is difficult for traditional synthesis processes to control the shape and size of materials, resulting in unstable performance.

Method used

The template agent is used to prevent particles from agglomerating, and lithium manganese iron phosphate composite positive electrode material is prepared by stirring reactions and ball milling, and the surface of the material is coated with polymer electrolyte to prevent side reactions.

Benefits of technology

The dispersion and electrical contactability of lithium manganese iron phosphate composite cathode material are improved, and the electrochemical performance is significantly improved, such as initial discharge capacity, cycle stability and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005183146650000101
    Figure BDA0005183146650000101
  • Figure BDA0005183146650000111
    Figure BDA0005183146650000111
Patent Text Reader

Abstract

The present invention belongs to the field of battery technology, and discloses a lithium iron manganese phosphate composite positive electrode material and its preparation method and application. The preparation method of the lithium iron manganese phosphate composite positive electrode material comprises the following steps: stirring and mixing a ferrous source, a manganese source, a lithium source, a phosphorus source and a solvent to obtain a mixed solution; mixing a template with the mixed solution, stirring and reacting, and aging to obtain a lithium iron manganese phosphate precursor; stirring and mixing an ether monomer, a conductive salt, a diluent and an initiator to obtain an electrolyte precursor solution; mixing the lithium iron manganese phosphate precursor with the electrolyte precursor solution, ball milling, and obtaining a composite precursor; pre-calcining and calcining the composite precursor, and grinding to obtain a lithium iron manganese phosphate composite positive electrode material. The present invention effectively prevents the side reaction between the lithium iron manganese phosphate composite positive electrode material and the sulfide solid electrolyte by coating the surface of the lithium iron manganese phosphate with a polymer electrolyte, thereby improving the electrical performance of the solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a manganese iron phosphate lithium composite positive electrode material and a preparation method and application thereof. Background Art

[0002] Under the current energy situation, the dependence of traditional automobiles on fossil resources has been increasing, leading to the increasingly severe shadow of the energy crisis. Faced with this severe reality challenge, lithium-ion batteries, as an important branch of new energy technology, have gradually become a hot topic of concern to people from all walks of life. In particular, pure electric vehicles, with their clean and environmentally friendly characteristics, are gradually winning wide recognition from the market and consumers. With the increasing global awareness of environmental protection, the development prospects of pure electric vehicles are highly anticipated. In order to accelerate this process, it is particularly important to improve the energy density of power lithium-ion batteries. Energy density is an important indicator for measuring battery performance, which is directly related to the cruising range and convenience of electric vehicles. Improving energy density means that the volume and weight of the battery can be reduced, thereby reducing the manufacturing cost of the whole vehicle, and it can also shorten the charging time to meet the needs of more consumers for rapid replenishment of electricity. In addition, high-energy-density power batteries have other positive effects: on the one hand, it can significantly increase the vehicle's mileage, so that car owners do not have to frequently look for charging piles during long-distance travel; on the other hand, high-density batteries can effectively slow down the rate of battery capacity decay, thereby extending the battery's service life, which is of great significance for reducing the cost of the entire life cycle. Therefore, major automakers and research institutions are stepping up the development of new batteries to cope with changes in the future energy landscape and ensure that pure electric vehicles can go further on the road of sustainable development.

[0003] The higher the energy density of lithium-ion batteries, the more energy is released when an explosion occurs, and the greater the damage caused. In recent years, due to the frequent occurrence of accidents such as spontaneous combustion and explosion of lithium-ion batteries, its safety issues have attracted much attention. However, most of the existing lithium-ion batteries are based on liquid electrolytes, so there is still a possibility of serious safety problems such as short circuit, leakage, spontaneous combustion, and explosion. When impacted or punctured, it is easy to explode. Therefore, it is urgent to develop new electrolytes. Due to its excellent ion conductivity, sulfide solid electrolytes have become the focus of attention of automobile companies and scientific research institutions.

[0004] All-solid-state batteries use inorganic solid compounds as electrolytes, and have the characteristics of high energy density and non-flammability, which can greatly improve their safety and energy density. Sulfide solid electrolytes are considered to be one of the ideal solid electrolyte materials. Although lithium iron manganese phosphate positive electrode materials have the advantages of both the good kinetics of LiFePO4 and the high energy density of LiMnPO4, the shape and size of the materials obtained by the traditional synthesis process are difficult to control, and most of the modification methods use high-temperature solid-phase methods, which makes the experimental cycle too long. At the same time, combining lithium iron manganese phosphate and sulfide solid electrolytes to develop new battery systems is a technical path with application prospects, but in the actual performance test process, significant side reactions will occur at the interface between the electrolyte and the electrode material, and the reaction products will adhere to the surface of the electrode material, seriously damaging the performance of the battery system.

[0005] Therefore, how to reduce or prevent the side reactions between electrolytes and electrode materials and improve battery performance is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a manganese iron phosphate lithium composite positive electrode material and a preparation method and application thereof. The manganese iron phosphate lithium composite positive electrode material prepared by the present invention can effectively prevent the side reaction between the lithium manganese iron phosphate and the sulfide solid electrolyte, thereby having better electrochemical performance, including higher initial discharge capacity, better cycle stability and higher rate performance.

[0007] The first aspect of the present invention provides a method for preparing a lithium manganese iron phosphate composite positive electrode material, comprising the following steps:

[0008] The ferrous source, the manganese source, the lithium source, the phosphorus source and the solvent are stirred and mixed to obtain a mixed solution;

[0009] The template agent is mixed with the mixed solution, stirred for reaction, and aged to obtain a lithium manganese iron phosphate precursor;

[0010] The ether monomer, the conductive salt, the diluent and the initiator are stirred and mixed to obtain an electrolyte precursor solution;

[0011] The lithium manganese iron phosphate precursor is mixed with an electrolyte precursor solution, and ball-milled to obtain a composite precursor;

[0012] The composite precursor is pre-sintered and calcined, and ground to obtain a lithium manganese iron phosphate composite positive electrode material.

[0013] In some embodiments of the present invention, the amounts of the ferrous source, manganese source, lithium source, and phosphorus source are based on the stoichiometric ratio of each element in lithium iron manganese phosphate, and the molecular formula of lithium iron manganese phosphate is LiMn x Fe1-x PO4, 0.1≤X≤0.9.

[0014] In some embodiments of the present invention, the rotation speed of the stirring reaction is 400-800 rpm; and / or, the temperature of the stirring reaction is 40-60° C.; and / or, the time of the stirring reaction is 1-3 h.

[0015] In some embodiments of the present invention, the aging time is 16-20 hours to ensure complete reaction.

[0016] In some embodiments of the present invention, after the aging, the method further comprises the steps of washing and drying the aged product.

[0017] In some embodiments of the present invention, the washing is performed using anhydrous ethanol, and the number of washing times is 1-3 times.

[0018] In some embodiments of the present invention, the ball milling time is 18-22 hours.

[0019] In some embodiments of the present invention, after the ball milling, the process further comprises the steps of filtering the ball milled slurry, collecting and drying the solid matter.

[0020] In some embodiments of the present invention, the pre-burning temperature rise rate is 4-6°C / min; and / or, the pre-burning temperature is 350-450°C; and / or, the pre-burning time is 250-350min.

[0021] In some embodiments of the present invention, the heating rate of the calcination is 9-11°C / min; and / or the calcination temperature is 750-850°C; and / or the calcination time is 700-750min.

[0022] In some embodiments of the present invention, the mass ratio of the mixed solution to the template is 10:(0.5-1).

[0023] In some embodiments of the present invention, the mass ratio of the ether monomer, the conductive salt, the diluent and the initiator is 1:(0.1-0.5):(0.01-0.03):(0.05-0.1).

[0024] In some embodiments of the present invention, the ferrous source includes at least one of ferrous oxalate, ferrous sulfate, and ferrous chloride, preferably ferrous oxalate, which can make the obtained lithium manganese iron phosphate composite positive electrode material have high crystallinity and strong bonding force, and avoid the introduction of impurities during the preparation process.

[0025] In some embodiments of the present invention, the manganese source includes at least one of manganese sulfate, manganese carbonate, and manganese tetraoxide.

[0026] In some embodiments of the present invention, the lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium oxalate.

[0027] In some embodiments of the present invention, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate.

[0028] In some embodiments of the invention, the solvent comprises water.

[0029] In some embodiments of the present invention, the templating agent comprises polyvinyl pyrrolidone.

[0030] In some embodiments of the present invention, the ether monomer includes at least one of 1,3-dioxolane, ethylene oxide, and 1,2-propylene oxide. 1,3-dioxolane is preferred. 1,3-dioxolane is used as a polymer monomer, and the product after polymerization can form a complex system with an alkali metal salt; since the main chain of this type of polymer contains a strong electron-donating group ether oxygen functional group, 1,3-dioxolane is a complex monomer with a better complexing effect after polymerization.

[0031] In some embodiments of the present invention, the conductive salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, and lithium bis(fluorosulfonyl)imide. Lithium trifluoromethanesulfonyl imide is preferred. Lithium bis(trifluoromethanesulfonyl)imide has a certain solubility in the polymer system, does not precipitate a single solid after the system is solidified, and has less corrosive effect on the positive electrode current collector.

[0032] In some embodiments of the present invention, the diluent includes at least one of trimethylolpropane triglycidyl ether, polyethylene glycol diglycidyl ether, and polypropylene glycol diglycidyl ether. Trimethylolpropane triglycidyl ether is preferably used as an active diluent for epoxy compounds, because epoxy compounds are easily polymerized by boron trifluoride catalysis. The reaction rate of boron trifluoride-catalyzed 1,3-dioxolane polymerization is relatively fast. In order to avoid the polymerization of the electrolyte precursor solution in the mixing tank, a small amount of trimethylolpropane triglycidyl ether is added to the epoxy compound to reduce the polymerization reaction activity, prolong the polymerization time, and ensure sufficient reaction.

[0033] In some embodiments of the present invention, the initiator includes at least one of lithium tetrafluoroborate, lithium difluorooxalatoborate, and lithium hexafluorophosphate. Lithium tetrafluoroborate is preferred because epoxy compounds are easily polymerized by boron trifluoride. Therefore, lithium tetrafluoroborate is selected to provide boron trifluoride to the system to catalyze the polymerization reaction of 1,3-dioxolane.

[0034] A second aspect of the present invention provides a lithium iron manganese phosphate composite positive electrode material, wherein the lithium iron manganese phosphate composite positive electrode material is prepared by the preparation method described in the first aspect of the present invention.

[0035] In some embodiments of the present invention, the lithium manganese iron phosphate composite positive electrode material includes lithium manganese iron phosphate and a polymer electrolyte, the polymer electrolyte is coated on at least a portion of the surface of the lithium manganese iron phosphate, and the raw materials for preparing the polymer electrolyte include ether monomers, conductive salts, diluents and initiators.

[0036] A third aspect of the present invention provides a solid-state battery, comprising the lithium manganese iron phosphate composite positive electrode material described in the second aspect of the present invention.

[0037] In some embodiments of the present invention, the solid-state battery is a solid-state lithium-ion battery, and further comprises a negative electrode material and a sulfide solid electrolyte.

[0038] In some embodiments of the present invention, the negative electrode material includes metallic lithium, graphite or silicon carbon.

[0039] In some embodiments of the present invention, the sulfide solid electrolyte includes Li6PS5Cl.

[0040] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0041] The present invention can prevent the agglomeration of particles during the synthesis process by using a template agent, thereby improving the dispersibility and electrical contact of the lithium manganese iron phosphate composite positive electrode material. The synthesized lithium manganese iron phosphate composite positive electrode material has better electrochemical properties, such as higher initial discharge capacity, better cycle stability and higher rate performance; the improvement of these properties is attributed to the improvement of morphology control, dispersibility and crystallinity.

[0042] The lithium iron manganese phosphate composite positive electrode material prepared by the preparation method of the present invention has a polymer electrolyte coated on the surface of the lithium iron manganese phosphate, which effectively prevents the side reaction between the lithium iron manganese phosphate composite positive electrode material and the sulfide solid electrolyte, and improves the electrical performance of the solid-state battery. DETAILED DESCRIPTION

[0043] The present invention is further described in detail below by specific examples. The raw materials, reagents or devices used in the examples can be obtained from conventional commercial sources or by prior art methods unless otherwise specified. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0044] Example 1

[0045] A method for preparing a lithium manganese iron phosphate composite positive electrode material comprises the following steps:

[0046] (1) According to lithium manganese iron phosphate (LiMn 0.4 Fe 0.6 PO4), using deionized water as solvent, weighing manganese sulfate and ferrous oxalate as raw materials, and preparing corresponding solutions; at the same time, preparing lithium oxalate solution and phosphoric acid solution of appropriate concentration;

[0047] (2) mixing the manganese sulfate solution, the ferrous oxalate solution and the lithium oxalate solution, and slowly pouring the mixture into the phosphoric acid solution while continuously stirring to obtain a mixed solution;

[0048] (3) adding vinyl pyrrolidone (PVP) as a template to the mixed solution of step (2) (wherein the mass ratio of the mixed solution to PVP is 10:1), stirring at 50° C. and 600 rpm for 2 h, aging for 18 h after the reaction, and then washing the aged product with anhydrous ethanol three times, and then drying it in a vacuum drying oven at 70° C. to obtain a lithium manganese iron phosphate precursor;

[0049] (4) 1,3-dioxolane, lithium bis(trifluoromethanesulfonyl imide) and trimethylolpropane triglycidyl ether were mixed and stirred for 2 h, and then lithium tetrafluoroborate was added (wherein the mass ratio of 1,3-dioxolane, lithium bis(trifluoromethanesulfonyl imide), trimethylolpropane triglycidyl ether and lithium tetrafluoroborate was 1:0.3:0.02:0.06), and stirred for 1.5 h to obtain an electrolyte precursor solution;

[0050] (5) adding the lithium manganese iron phosphate precursor obtained in step (3) to the electrolyte precursor solution obtained in step (4), and then placing the mixture in a ball mill for 20 hours. After preliminary drying by suction filtration, the milled slurry is placed in a vacuum drying oven at 70° C. to obtain a composite precursor;

[0051] (6) placing the composite precursor obtained in step (5) into a quartz boat and placing it in a muffle furnace, first heating it to 400° C. at a heating rate of 5° C. / min, pre-calcining it for 300 min, then heating it to 800° C. at a heating rate of 10° C. / min, and calcining it for 720 min;

[0052] (7) The product after calcination in step (6) was allowed to cool naturally to room temperature, and the obtained product was taken out and ground in a mortar for 30 minutes to obtain a manganese iron phosphate lithium composite positive electrode material.

[0053] Example 2

[0054] A method for preparing a lithium manganese iron phosphate composite positive electrode material comprises the following steps:

[0055] (1) According to lithium manganese iron phosphate (LiMn 0.4 Fe 0.6PO4), using deionized water as solvent, weighing manganese carbonate and ferrous oxalate as raw materials, and preparing corresponding solutions; at the same time, preparing lithium oxalate solution and phosphoric acid solution of appropriate concentration;

[0056] (2) mixing the manganese carbonate solution, the ferrous oxalate solution and the lithium oxalate solution, and slowly pouring the mixture into the phosphoric acid solution while continuously stirring to obtain a mixed solution;

[0057] (3) adding vinyl pyrrolidone (PVP) as a template to the mixed solution of step (2) (wherein the mass ratio of the mixed solution to PVP is 10:1), stirring at 50° C. and 600 rpm for 2 h, aging for 18 h after the reaction, and then washing the aged product with anhydrous ethanol three times, and then drying it in a vacuum drying oven at 70° C. to obtain a lithium manganese iron phosphate precursor;

[0058] (4) 1,3-dioxolane, lithium bis(trifluoromethanesulfonyl imide) and trimethylolpropane triglycidyl ether were mixed and stirred for 2 h, and then lithium tetrafluoroborate was added (wherein the mass ratio of 1,3-dioxolane, lithium bis(trifluoromethanesulfonyl imide), trimethylolpropane triglycidyl ether and lithium tetrafluoroborate was 1:0.3:0.02:0.06), and stirred for 1.5 h to obtain an electrolyte precursor solution;

[0059] (5) adding the lithium manganese iron phosphate precursor obtained in step (3) to the electrolyte precursor solution obtained in step (4), and then placing the mixture in a ball mill for 20 hours. After preliminary drying by suction filtration, the milled slurry is placed in a vacuum drying oven at 70° C. to obtain a composite precursor;

[0060] (6) placing the composite precursor obtained in step (5) into a quartz boat and placing it in a muffle furnace, first heating it to 400° C. at a heating rate of 5° C. / min, pre-calcining it for 300 min, then heating it to 800° C. at a heating rate of 10° C. / min, and calcining it for 720 min;

[0061] (7) The product after calcination in step (6) was allowed to cool naturally to room temperature, and the obtained product was taken out and ground in a mortar for 30 minutes to obtain a manganese iron phosphate lithium composite positive electrode material.

[0062] Example 3

[0063] A method for preparing a lithium manganese iron phosphate composite positive electrode material comprises the following steps:

[0064] (1) According to lithium manganese iron phosphate (LiMn 0.4 Fe 0.6PO4), using deionized water as solvent, weighing manganese tetraoxide and ferrous sulfate as raw materials, and preparing corresponding solutions; at the same time, preparing lithium oxalate solution and phosphoric acid solution of appropriate concentration;

[0065] (2) mixing the manganese tetraoxide solution, the ferrous sulfate solution and the lithium oxalate solution, and slowly pouring the mixture into the phosphoric acid solution while continuously stirring to obtain a mixed solution;

[0066] (3) adding vinyl pyrrolidone (PVP) as a template to the mixed solution of step (2) (wherein the mass ratio of the mixed solution to PVP is 10:1), stirring at 50° C. and 600 rpm for 2 h, aging for 18 h after the reaction, and then washing the aged product with anhydrous ethanol three times, and then drying it in a vacuum drying oven at 70° C. to obtain a lithium manganese iron phosphate precursor;

[0067] (4) 1,3-dioxolane, lithium bis(trifluoromethanesulfonyl imide) and trimethylolpropane triglycidyl ether were mixed and stirred for 2 h, and then lithium tetrafluoroborate was added (wherein the mass ratio of 1,3-dioxolane, lithium bis(trifluoromethanesulfonyl imide), trimethylolpropane triglycidyl ether and lithium tetrafluoroborate was 1:0.3:0.02:0.06), and stirred for 1.5 h to obtain an electrolyte precursor solution;

[0068] (5) adding the lithium manganese iron phosphate precursor obtained in step (3) to the electrolyte precursor solution obtained in step (4), and then placing the mixture in a ball mill for 20 hours. After preliminary drying by suction filtration, the milled slurry is placed in a vacuum drying oven at 70° C. to obtain a composite precursor;

[0069] (6) placing the composite precursor obtained in step (5) into a quartz boat and placing it in a muffle furnace, first heating it to 400° C. at a heating rate of 5° C. / min, pre-calcining it for 300 min, then heating it to 800° C. at a heating rate of 10° C. / min, and calcining it for 720 min;

[0070] (7) The product after calcination in step (6) was allowed to cool naturally to room temperature, and the obtained product was taken out and ground in a mortar for 30 minutes to obtain a manganese iron phosphate lithium composite positive electrode material.

[0071] Comparative Example 1

[0072] A method for preparing a lithium manganese iron phosphate positive electrode material comprises the following steps:

[0073] (1) According to lithium manganese iron phosphate (LiMn 0.4 Fe 0.6PO4), using deionized water as solvent, weighing manganese carbonate and ferrous oxalate as raw materials, and preparing corresponding solutions; at the same time, preparing lithium oxalate solution and phosphoric acid solution of appropriate concentration;

[0074] (2) mixing the manganese carbonate solution, the ferrous oxalate solution and the lithium oxalate solution, and slowly pouring them into the phosphoric acid solution, stirring at 50° C. and 600 rpm for 2 h, and then aging for 18 h after the reaction, and then washing the aged product with anhydrous ethanol for 3 times, and then drying it in a vacuum drying oven at 70° C. to obtain a lithium iron manganese phosphate precursor;

[0075] (3) 1,3-dioxolane, lithium bis(trifluoromethanesulfonyl imide) and trimethylolpropane triglycidyl ether were mixed and stirred for 2 h, and then lithium tetrafluoroborate was added (wherein the mass ratio of 1,3-dioxolane, lithium bis(trifluoromethanesulfonyl imide), trimethylolpropane triglycidyl ether and lithium tetrafluoroborate was 1:0.3:0.02:0.06), and stirred for 1.5 h to obtain an electrolyte precursor solution;

[0076] (4) adding the lithium manganese iron phosphate precursor obtained in step (2) to the electrolyte precursor solution obtained in step (3), and then placing the mixture in a ball mill for 20 hours. After the milled slurry is initially dried by suction filtration, it is then placed in a vacuum drying oven at 70° C. to obtain a composite precursor;

[0077] (5) placing the composite precursor obtained in step (4) into a quartz boat and placing it in a muffle furnace, first heating it to 400° C. at a heating rate of 5° C. / min, pre-calcining it for 300 min, then heating it to 800° C. at a heating rate of 10° C. / min, and calcining it for 720 min;

[0078] (6) The product after calcination in step (5) was allowed to cool naturally to room temperature, and the obtained product was taken out and ground in a mortar for 30 minutes to obtain a lithium manganese iron phosphate positive electrode material.

[0079] Comparative Example 2

[0080] A method for preparing a lithium manganese iron phosphate positive electrode material comprises the following steps:

[0081] (1) According to lithium manganese iron phosphate (LiMn 0.4 Fe 0.6 PO4), using deionized water as solvent, weighing manganese sulfate and ferrous oxalate as raw materials, and preparing corresponding solutions; at the same time, preparing lithium oxalate solution and phosphoric acid solution of appropriate concentration;

[0082] (2) mixing the manganese sulfate solution, the ferrous oxalate solution and the lithium oxalate solution, and slowly pouring the mixture into the phosphoric acid solution while continuously stirring;

[0083] (3) adding vinyl pyrrolidone (PVP) as a template to the mixed solution of step (2) (wherein the mass ratio of the mixed solution to PVP is 10:1), stirring at 50° C. and 600 rpm for 2 h, aging for 18 h after the reaction, and then washing the aged product with anhydrous ethanol three times, and then drying it in a vacuum drying oven at 70° C. to obtain a lithium manganese iron phosphate precursor;

[0084] (4) placing the lithium manganese iron phosphate precursor obtained in step (3) into a quartz boat and placing it in a muffle furnace, first heating it to 400° C. at a heating rate of 5° C. / min, pre-calcining it for 300 min, then heating it to 800° C. at a heating rate of 10° C. / min, and calcining it for 720 min;

[0085] (5) The product after calcination in step (4) was allowed to cool naturally to room temperature, and the obtained product was taken out and ground in a mortar for 30 minutes to obtain a lithium manganese iron phosphate positive electrode material.

[0086] Comparative Example 3

[0087] A method for preparing a lithium manganese iron phosphate positive electrode material comprises the following steps:

[0088] (1) According to lithium manganese iron phosphate (LiMn 0.4 Fe 0.6 PO4), using deionized water as solvent, weighing manganese sulfate and ferrous oxalate as raw materials, and preparing corresponding solutions; at the same time, preparing lithium oxalate solution and phosphoric acid solution of appropriate concentration;

[0089] (2) mixing the manganese sulfate solution, the ferrous oxalate solution and the lithium oxalate solution, and slowly pouring them into the phosphoric acid solution, stirring and reacting at 50° C. and 600 rpm for 2 h, and then aging for 18 h after the reaction, and then washing the aged product with anhydrous ethanol for 3 times, and then drying it in a vacuum drying oven at 70° C. to obtain a lithium iron manganese phosphate precursor;

[0090] (3) placing the lithium manganese iron phosphate precursor obtained in step (2) into a quartz boat and placing it in a muffle furnace, first heating it to 400° C. at a heating rate of 5° C. / min, pre-calcining it for 300 min, then heating it to 800° C. at a heating rate of 10° C. / min, and calcining it for 720 min;

[0091] (4) The product after calcination in step (3) is allowed to cool naturally to room temperature, and the obtained product is taken out and ground in a mortar for 30 minutes to obtain a lithium manganese iron phosphate positive electrode material.

[0092] Product performance test:

[0093] The lithium iron manganese phosphate composite positive electrode material obtained in Example 1-3 and the lithium iron manganese phosphate positive electrode material obtained in Comparative Example 1-3 are respectively used as positive electrode materials to assemble a solid-state battery, and the steps are as follows:

[0094] (1) Preparation of positive electrode: The positive electrode, measured by mass percentage, is lithium manganese iron phosphate (LiMn 0.4 Fe 0.6 PO4) content is 70%, the content of solid electrolyte (Li6PS5Cl) is 28%, and the content of conductive agent (VGCF) is 2%; in a glove box filled with argon, the above materials are placed in a mortar and ground for 10-20 minutes according to proportion until they are evenly mixed to obtain a composite positive electrode;

[0095] (2) Solid electrolyte: The solid electrolyte is lithium phosphorus sulfur chloride (Li6PS5Cl);

[0096] (3) Assembly of all-solid-state battery: First, weigh 0.1g Li6PS5Cl solid electrolyte powder and place it in a mold sleeve, cold press it at 360MPa for 3-5min to obtain a sulfide solid electrolyte layer, then lay the positive electrode and negative electrode on both sides of the sulfide solid electrolyte layer, and then cold press it at 50MPa pressure, and finally tighten the screws to seal the mold to obtain an all-solid-state battery. Among them, the negative electrodes corresponding to the positive electrode materials of Examples 1-3 are metallic lithium, graphite and silicon carbon respectively; the negative electrodes corresponding to the positive electrode materials of Comparative Examples 1-3 are all metallic lithium.

[0097] Each group of solid-state lithium-ion batteries obtained above was charged and discharged at 0.1C, and a 0.1C charge and discharge cycle test was performed under the condition that the charge and discharge cut-off voltage was 2.75-4.3V. The results are shown in Table 1.

[0098] Table 1 Test results of solid-state lithium-ion batteries

[0099]

[0100]

[0101] It can be seen from the data in Table 1 that when the lithium iron manganese phosphate composite positive electrode material prepared by the method of the present invention is used to make a positive electrode and the positive electrode is used to assemble a solid-state battery, the solid-state battery has a 0.1C discharge capacity of up to 138 mAh / g, and a capacity retention rate of 88% after 100 cycles of 0.1C. The solid-state battery based on the lithium iron manganese phosphate positive electrode material prepared by the template method in Comparative Example 1 has a 0.1C discharge capacity of 123 mAh / g; in Comparative Example 2, the surface of the positive electrode material is not coated with a polymer electrolyte, and in Comparative Example 3, the template method is not used for preparation and the surface coating method is not used to modify the material, resulting in a side reaction between the positive electrode and the sulfide solid electrolyte, resulting in 0.1C discharge capacities of 92 mAh / g and 81 mAh / g, respectively. This shows that the present invention uses a template to synthesize the lithium iron manganese phosphate material and simultaneously coats a layer of polymer electrolyte on its surface, thereby effectively improving the conductivity of the lithium iron manganese phosphate material and inhibiting the growth and agglomeration of crystal particles, so that the lithium ion battery containing the lithium iron manganese phosphate composite positive electrode material of the present invention has excellent rate performance and a high discharge specific capacity, while preventing the lithium iron manganese phosphate from contacting with the sulfide solid electrolyte to produce side reactions, thereby avoiding the side reactions affecting the battery performance.

[0102] The preferred embodiments of the present invention are specifically described above, but the invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.

Claims

1. A method for preparing a lithium manganese iron phosphate composite positive electrode material, characterized in that: The following steps are involved: The ferrous source, the manganese source, the lithium source, the phosphorus source and the solvent are stirred and mixed to obtain a mixed solution; The template agent is mixed with the mixed solution, stirred for reaction, and aged to obtain a lithium manganese iron phosphate precursor; The ether monomer, the conductive salt, the diluent and the initiator are stirred and mixed to obtain an electrolyte precursor solution; The lithium manganese iron phosphate precursor is mixed with an electrolyte precursor solution, and ball-milled to obtain a composite precursor; The composite precursor is pre-sintered and calcined, and ground to obtain a lithium manganese iron phosphate composite positive electrode material.

2. The preparation method according to claim 1, characterized in that: The amounts of the ferrous source, manganese source, lithium source and phosphorus source are based on the stoichiometric ratio of each element in lithium iron manganese phosphate, the molecular formula of which is LiMn x Fe 1-x PO4, 0.1≤X≤0.

9.

3. The preparation method according to claim 1, characterized in that: The rotation speed of the stirring reaction is 400-800 rpm; and / or, the temperature of the stirring reaction is 40-60° C.; and / or, the time of the stirring reaction is 1-3 h.

4. The preparation method according to claim 1, characterized in that: The aging time is 16-20h.

5. The preparation method according to claim 1, characterized in that: The pre-burning temperature rise rate is 4-6°C / min; and / or, the pre-burning temperature is 350-450°C; and / or, the pre-burning time is 250-350min.

6. The preparation method according to claim 1, characterized in that: The heating rate of the calcination is 9-11°C / min; and / or, the calcination temperature is 750-850°C; and / or, the calcination time is 700-750min.

7. The preparation method according to claim 1, characterized in that: The ferrous source includes at least one of ferrous oxalate, ferrous sulfate, and ferrous chloride; and / or, the manganese source includes at least one of manganese sulfate, manganese carbonate, and manganese tetraoxide; and / or, the lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium oxalate; and / or, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate.

8. The preparation method according to claim 1, characterized in that: The template agent includes polyvinyl pyrrolidone.

9. A lithium manganese iron phosphate composite positive electrode material, characterized in that: The lithium manganese iron phosphate composite positive electrode material is prepared by the preparation method according to any one of claims 1 to 6.

10. A solid-state battery, characterized in that: The solid-state battery comprises the lithium manganese iron phosphate composite positive electrode material according to claim 9.